Earth Empire and Sacred Text - Mahan Mirza (International Institute of Islamic Thought, 2011)
There is a new trend in the progressive quarter of American Evangelical Christianity to form common bonds with Muslims. From this impulse stem books such as Miroslav Volf’s Allah: A Christian Response and Carl Medearis’ Muslims, Christians, and Jesus: Gaining Understanding and Building Relationships, as well as organizations such as Rick Love’s Peace Catalyst and Yale Divinity School’s Reconciliation Program. David Johnston’s robust Earth, Empire and Sacred Text falls within this trend (although these are by no means monolithic attempts and each must be evaluated on its own terms). As an Evangelical Christian with an academic streak and extensive international experience, Johnston is uniquely positioned to not only reach out to Muslims but also to educate his fellow American Christians. The book is an extraordinary undertaking and may be considered a three-volume work collapsed into one. Devout yet pragmatic, Johnston is prepared to engage the reality of the world in order develop a theology that acknowledges its own limitations. Johnston combines intellectual rigor with political activism, while remaining theologically inclusive yet authentic ...